2021
DOI: 10.26716/jcsi.2021.10.8.33
|View full text |Cite
|
Sign up to set email alerts
|

Preparing School Leaders to Advance Equity in Computer Science Education

Abstract: <p><strong>Background and Context:</strong> Most large-scale statewide initiatives of the Computer Science for All (CS for All) movement have focused on the classroom level. Critical questions remain about building school and district leadership capacity to support teachers while implementing equitable computer science education that is scalable and sustainable.</p> <p><strong>Objective:</strong> This statewide research-practice partnership, involving university resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Third, using curriculum-agnostic, pre-existing materials allowed the workshops to move faster and more economically than building our own materials would have. Our findings echo previous research showing that administrators find value in equity-focused, example-based, discussion-oriented workshops that incorporate networking opportunities [7].…”
Section: Resultssupporting
confidence: 88%
“…Third, using curriculum-agnostic, pre-existing materials allowed the workshops to move faster and more economically than building our own materials would have. Our findings echo previous research showing that administrators find value in equity-focused, example-based, discussion-oriented workshops that incorporate networking opportunities [7].…”
Section: Resultssupporting
confidence: 88%
“…Establishing dedicated accessibility services and support staff ensures students with disabilities can access the necessary resources and assistance. This includes providing academic accommodations, facilitating accessible course materials, and offering personalized support (Flapan, Ryoo, Hadad, & Knudson, 2021).…”
Section: Institutional Support and Policy Implicationsmentioning
confidence: 99%
“…Students that experience marginalization due to their race or ethnicity are more likely to be enrolled in a school that does not offer a computer science course (Flapan, Ryoo, Hadad, & Knudson, 2021). Villavicencio et al (2018) suggested that schools serving students of color and those experiencing poverty may be prioritizing more pressing challenges such as absenteeism, limited resources, and low achievement in math and reading.…”
Section: The Current State Of Computing Educationmentioning
confidence: 99%